2022
DOI: 10.34067/kid.0008152021
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder and Post-Traumatic Growth following Kidney Transplantation

Abstract: Background: Kidney transplantation (KT) is a life-saving therapy for kidney failure. However, KT recipients can suffer from debilitating depression, post-traumatic stress disorder (PTSD), and suicide. In contrast to PTSD, post-traumatic growth (PTG) is a positive psychological change in response to a challenging situation. PTG has been studied in other chronic diseases, but less is known about its role in the setting of KT. We sought to elucidate the prevalence, predictors, and the impact of PTSD and PTG on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…At a median age of 25.7 years, 25 out of 42 adults after pediatric transplantation stated that they felt anxiety or were depressed in a study from Kärrfelt et al [29]. On the other hand, it was reported that psychological distress and post-traumatic stress disorder could result in "post traumatic growth", de ned as a positive and motivating psychological chance leading to positive coping strategies [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a median age of 25.7 years, 25 out of 42 adults after pediatric transplantation stated that they felt anxiety or were depressed in a study from Kärrfelt et al [29]. On the other hand, it was reported that psychological distress and post-traumatic stress disorder could result in "post traumatic growth", de ned as a positive and motivating psychological chance leading to positive coping strategies [15].…”
Section: Discussionmentioning
confidence: 99%
“…Other publications have investigated the impact of other chronic diseases on psychological distress in children and adolescents (e.g., cancer, diabetes, liver transplantation, lung transplantation, heart transplantation) [12][13][14]. Additionally, psychological distress had also been studied in adults suffering from chronic kidney failure on dialysis or after being transplanted [15]. However, little is known about psychological distress in adult persons after successful pediatric kidney transplantation during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…In more complex cases, irrespective of one's personality framework, the "cancer" event itself can trigger both acute distress (in its mildest forms) and adjustment disorder (following the diagnosis and processing process), all the way up to true post-traumatic stress, especially if the diagnosis is more unfavorable or not adequately managed by the clinical and family network. Therefore, the need to support the patient and family, from the earliest stages of the illness, is central to the healing process (including through cycles of psychotherapy and parental training techniques) and especially in the future perspective, and unfortunately, both in medical practice and in the literature, such profiles are often underestimated or relegated to mere services offered on par with organizational refreshments, effectively distorting the valuable clinical intervention on the cognitive and psychological sphere of the actors involved in the clinical stage [67][68][69][70][71][72][73][74][75].…”
Section: Psychological Implicationsmentioning
confidence: 99%